Kelaziman Kesalahan Berbahasa dalam Menulis Laporan Penelitian - Nyoto Hardjono (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
Language is the main media to deliver an idea. The mistakes in the language used will produce the wrong idea. To avoid the wrong idea, it is not allowed to make a mistake in using the language. The fact found in PGSD – FKIP UKSW bachelor degree students’ experiment report shows there are lots of repeating mistakes. The common mistakes found in grammatical aspect, such as: 1) The mistakes in differentiating between preposition and prefix; 2) the mistakes in forming words, and 3) the mistakes in constructing sentences. Common mistakes happen in spelling, especially in writing the title and notes, and the last is in the diction aspect. The common mistakes in diction usually happen with the use of inefficient words, improper word meaning, and the use of function words.